1967
DOI: 10.1136/adc.42.224.341
|View full text |Cite
|
Sign up to set email alerts
|

Sugar malabsorption due to deficiencies of disaccharidase activities and of monosaccharide transport.

Abstract: In many societies including our own, carbohydrates play a major part in the total calorie supply. According to the National Food survey figures (Greaves and Hollingsworth, 1964), the average daily diet of adults contains nearly 350 g. of this constituent. Diets of course vary with eating habits and social class, but the dietary carbohydrates are largely ingested as poly-, oligo-, and disaccharides. In the very young, however, the carbohydrate intake may consist almost entirely of disaccharides, though this pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0
4

Year Published

1969
1969
1996
1996

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 69 publications
2
14
0
4
Order By: Relevance
“…Davidson in 1967 suggested that estimation of the pH of fresh stools was of value as a screening test for disaccharide malabsorption, but others considered such an estimation was not reliable (Holzel, 1967).…”
mentioning
confidence: 99%
“…Davidson in 1967 suggested that estimation of the pH of fresh stools was of value as a screening test for disaccharide malabsorption, but others considered such an estimation was not reliable (Holzel, 1967).…”
mentioning
confidence: 99%
“…Hypolactasia In many animal species, levels of intestinal lactase diminish with age. A similar tendency seems to occur in man, especially in some racial groups (Holzel, 1967). Occasionally in children, and perhaps more commonly in adults, isolated hypolactasia may cause diarrhoea.…”
mentioning
confidence: 64%
“…In only 2 of the 7 patients in whom mucosal enzyme assays were attempted was there apparently a history of diarrhoea after the first breast-milk feeding (Launiala, Kuitunen, and Visakorpi, 1966). Three were in older children.…”
Section: Methodsmentioning
confidence: 99%
“…The two infants recorded by Launiala et al (1966) were both observed in hospital from the third week of life. Peroral biopsies from the distal duodenum in the 3rd and 5th month of life, respectively, showed no lactase activities in either, when quantitatively assayed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation